2021
DOI: 10.3390/cancers13040614
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Oncolytic Virotherapy for Glioblastoma: In Search of Biomarkers for Response

Abstract: Oncolytic virus (OV) treatment may offer a new treatment option for the aggressive brain tumor glioblastoma. Clinical trials testing oncolytic viruses in this patient group have shown promising results, with patients achieving impressive long-term clinical responses. However, the number of responders to each OV remains low. This is thought to arise from the large heterogeneity of these tumors, both in terms of molecular make-up and their immune-suppressive microenvironment, leading to variability in responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 177 publications
0
22
0
3
Order By: Relevance
“…An ex vivo 3D tumor model generated from fresh tissue provides a culture condition that supports further researches into the dynamics of viral infection and the interaction with local immune system in the specific tumor microenvironment (304). With application of this system, it is possible to screen multiple OVs for a specific patient and establish the optimal OVT (224). Undoubtedly, identifying the optimal dosing, route of administration and schedule in OVs treatment requires further investigation.…”
Section: Future Directionsmentioning
confidence: 96%
See 1 more Smart Citation
“…An ex vivo 3D tumor model generated from fresh tissue provides a culture condition that supports further researches into the dynamics of viral infection and the interaction with local immune system in the specific tumor microenvironment (304). With application of this system, it is possible to screen multiple OVs for a specific patient and establish the optimal OVT (224). Undoubtedly, identifying the optimal dosing, route of administration and schedule in OVs treatment requires further investigation.…”
Section: Future Directionsmentioning
confidence: 96%
“…Using OVs with knowledge of the specific mechanisms of their action will greatly benefit the OVT: appropriate markers can provide information about whether these mechanisms are working or not. More details on potential biomarkers for OVs in GBM were recently reviewed by Stavrakaki et al (224).…”
Section: Finding Suitable Markers For Evaluating the Effectiveness Of Therapymentioning
confidence: 99%
“…Although oncolytic viruses can infect both normal and cancer cells, they can only replicate in cancer cells[ 217 ]. Preclinical and clinical trials have pointed to the capability of oncolytic viruses to stimulate antitumor immune responses by recruiting T cells (reviewed in[ 218 , 219 ]). It has been reported that the Zika virus exerts oncolytic activity against GSCs.…”
Section: Discussionmentioning
confidence: 99%
“…There is not, however, a generally accepted molecular biomarker used to predict response, though the following are associated with treatment response: tumor receptor expression, tumor mutation burden, and alterations to several molecular pathways including IFN expression, autophagy, and ubiquitination. 3,71,76,77 While only proposed, these data points may offer an insight into virus selection and response to treatment. Concerns remain about dosing protocols, genetic stability, viral integrity after replication, off-target replication, and immune-mediated clearance of OVs.…”
Section: Intratumoralmentioning
confidence: 99%